2005
DOI: 10.1158/0008-5472.can-05-1840
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hsp27 after Androgen Ablation Facilitates Androgen-Independent Progression in Prostate Cancer via Signal Transducers and Activators of Transcription 3–Mediated Suppression of Apoptosis

Abstract: One strategy to improve therapies in prostate cancer involves targeting cytoprotective genes activated by androgen withdrawal to delay the emergence of the androgen-independent (AI) phenotype. The objectives of this study were to define changes in Hsp27 levels after androgen ablation and to evaluate the functional relevance of these changes in AI progression. Using a tissue microarray of 232 specimens of hormone-naïve and post-hormone ablation-treated prostate cancer, we found that Hsp27 levels increase after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
209
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 202 publications
(218 citation statements)
references
References 41 publications
8
209
1
Order By: Relevance
“…Collectively, these findings show that Hsp27 helps mediate bladder cancer progression and development of treatment resistance to cytotoxic chemotherapy. The response to OGX-427 in UMUC-3 cells are similar to our previous reports of Hsp27 knockdown in LNCaP and PC-3 prostate cancer cell lines (18,37). In these studies, OGX-427 enhanced the in vivo effects of castration-induced regression to delay androgen-independent LNCaP and PC-3 tumor growth and also enhances chemotherapy in vivo, emphasizing the additive role this ASO has in combination therapy regimes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Collectively, these findings show that Hsp27 helps mediate bladder cancer progression and development of treatment resistance to cytotoxic chemotherapy. The response to OGX-427 in UMUC-3 cells are similar to our previous reports of Hsp27 knockdown in LNCaP and PC-3 prostate cancer cell lines (18,37). In these studies, OGX-427 enhanced the in vivo effects of castration-induced regression to delay androgen-independent LNCaP and PC-3 tumor growth and also enhances chemotherapy in vivo, emphasizing the additive role this ASO has in combination therapy regimes.…”
Section: Discussionsupporting
confidence: 88%
“…Hsp27 can exert its antiapoptotic effects through the enhancement of nuclear factor-nB activity, by facilitating proteasomal degradation of its main inhibitor I-nB (36). Finally, we recently reported that Hsp27 interacts with and increases signal transducers and activators of transcription 3 levels and activity, a relevant transcription factor in many cancers, identifying yet another cytoprotective mechanism OGX-427 Down-regulation of Hsp27 in Bladder Cancer mediated by Hsp27 (37). Thus, Hsp27 is an attractive therapeutic target because its inhibition would affect multiple different pathways implicated in cancer cell survival and resistance as opposed to targeting a single pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotides against NF-jB p50, NF-jB p65, STAT1, STAT3, and control scrambled oligonucleotides were synthesized by phosphoroamidite chemistry, as described previously [42,47,48]. The keratinocytes were transfected with the indicated oligonucleotides (each 0.2 lM) premixed with Fugene 6 in KGM for 6 h. The cells were treated with high-calcium KBM for 48 h, and then incubated with 10 ng/mL IL-1b and/or the indicated concentrations of IL-12, IL-23, or IL-27.…”
Section: Treatment With Antisense Oligonucleotidesmentioning
confidence: 99%
“…For example, protection from apoptotic stress can be elicited through AR-dependent induction of heat shock protein 27 (HSP27) phosphorylation, or via expression of the protease ADAM9. 60,61 In addition, AR is known to directly induce activation of the clusterin locus, which encodes a molecular chaperone whose actions can be either cytoprotective or pro-apoptotic, dependent on the isoform induced. Specifically, androgen induces expression of the cytoprotective isoform 2, yet downregulates isoform 1 expression.…”
Section: Influence Of Ar On Prostate Cancer Cell Survivalmentioning
confidence: 99%